Comparison of PID and Fuzzy Controller for Position Control of AR.Drone - A Prayitno; V Indrawati; I I Trusulaw (Proceeding of the Electrical Engineering Computer Science and Informatics, 2016)
This  paper  describes  the  implementation  of  the  PID  Controller  to  control  the position of the AR.Drone in the x-y-z. This position control scheme uses three PID controllers to maintain the position of x, y and z using the signal control pitch, roll and vertical rate. PID Controller implemented on AR.Drone 2.0 and then tested in an indoor space. The performance of the  controller  will  be  compared  with  Fuzzy  Logic  Controller  schemes  that  have  been implemented previously. The results show that the PID Controller generate a response with rise time less than 3 seconds at the x and y position with around 25% overshoot. The result for z position give better result without overshoot.   The comparison between fuzzy logic and PID Controller indicates that the results of the PID controller is better although there is overshoot.